2013
DOI: 10.3746/jkfn.2013.42.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Effects of Orostachys japonicus with Medicinal Herbs in Streptozotocin-Induced Diabetic Rats

Abstract: The hypoglycemic and hypolipidemic effects from Wa-song (Orostachys japonicus) extracts with mixtures of medicinal herbs (such as Baekbokyung, Changchul and Sa-in) were evaluated in the streptozotocin (STZ)-induced diabetic rats. Thirty-five Sprague-Dawley rats were assigned to five groups; normal, diabetic control (D-control), a group fed a medicinal herbs mixture (D-MH), and a group fed composites of O. japonicus with mixtures of medicinal herbs (1:1, D-MHOA and 3:1, D-MHOB). All were fed on their diet for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Orostachys japonicus A. Berger (Crassulaceae) (OJ), also known as Wa-song in Korea, is used as a folk medication; its main habitat is on the surface of mountain rocks in Korea and Japan. OJ is a medicinal plant with immunoregulatory, anti-febrile, antidote, and anticancer activities (Jin Kwon and Kwangsoo Han, 2004;Kim et al, 2011;Lee et al, 2011;Ryu et al, 2014;Ryu et al, 2012;Shin et al, 2013;Yoon et al, 2000). It is reported that OJ increased CD4-and CD8-T cells and the production of interferon γ in BALB/c mice (Jin Kwon and Kwangsoo Han, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Orostachys japonicus A. Berger (Crassulaceae) (OJ), also known as Wa-song in Korea, is used as a folk medication; its main habitat is on the surface of mountain rocks in Korea and Japan. OJ is a medicinal plant with immunoregulatory, anti-febrile, antidote, and anticancer activities (Jin Kwon and Kwangsoo Han, 2004;Kim et al, 2011;Lee et al, 2011;Ryu et al, 2014;Ryu et al, 2012;Shin et al, 2013;Yoon et al, 2000). It is reported that OJ increased CD4-and CD8-T cells and the production of interferon γ in BALB/c mice (Jin Kwon and Kwangsoo Han, 2004).…”
Section: Introductionmentioning
confidence: 95%